Geriatric patients in emergency and intensive care medicine - Singler, Katrin; Christ, M.; Sieber, Cornel; Gosch, M.; Heppner, Hans Jürgen (Internist, 2011)
The democratic shift poses new challenges in emergency medicine and intensive care. Old patients call for special needs that have to be taken into consideration during treatment. Due to the heterogeneity in this patient group biological age plays an important role. Mortality among old patients is high, but functionality and comorbidity have a great effect on patient outcome. Structural and functional organ changes have an additional impact on the treatment of geriatric patients in emergency medicine and intensive care. Therefore, basic geriatric knowledge should be part of the curricula of both, intensive care and emergency medicine.
Keywords: Geriatric patient; Intensive care; Emergency medicine; Functionality; Multimorbidity